2020
DOI: 10.3934/dcdss.2020018
|View full text |Cite
|
Sign up to set email alerts
|

On a parabolic-elliptic chemotaxis-growth system with nonlinear diffusion

Abstract: This paper considers the following parabolic-elliptic chemotaxisgrowth system with nonlinear diffusion ut = ∇ • (D(u)∇u) − ∇ • (χu q ∇v) + µu(1 − u α), x ∈ Ω, t > 0, 0 = ∆v − v + u γ , x ∈ Ω, t > 0 under homogeneous Neumann boundary conditions for some constants q ≥ 1, α > 0 and γ ≥ 1, where D(u) ≥ c D u m−1 (m ≥ 1) for all u > 0 and D(u) > 0 for all u ≥ 0, and Ω ⊂ R N (N ≥ 1) is a bounded domain with smooth boundary. It is shown that when m > q + γ − 2 N , or α > q + γ − 1, or α = q + γ − 1 and µ > µ * , wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…(We also mention [16, 28] for the critical analysis on both blowing‐up and global solutions to Keller–Segel systems with super and sublinear stimulus production.) Further, for B , C , D and E as above but for A(u,v,w)uq1$A(u,v,w)\simeq u^{q-1}$, q1$q\ge 1$, in [25] it is shown that there exists μ=μ(m,q,χ,α,n)0$\mu ^*=\mu ^*(m,q,\chi ,\alpha ,n)\ge 0$ such that when q>m+γ2n$q >m + \gamma -\frac{2}{n}$ or α>m+γ1$\alpha > m + \gamma -1$ or α=m+γ1$\alpha = m + \gamma -1$ and μ>μ$\mu >\mu ^*$ system (1.1) possesses a global bounded classical solution for any sufficiently smooth initial data.…”
Section: Introduction and Presentation Of The Main Resultsmentioning
confidence: 99%
“…(We also mention [16, 28] for the critical analysis on both blowing‐up and global solutions to Keller–Segel systems with super and sublinear stimulus production.) Further, for B , C , D and E as above but for A(u,v,w)uq1$A(u,v,w)\simeq u^{q-1}$, q1$q\ge 1$, in [25] it is shown that there exists μ=μ(m,q,χ,α,n)0$\mu ^*=\mu ^*(m,q,\chi ,\alpha ,n)\ge 0$ such that when q>m+γ2n$q >m + \gamma -\frac{2}{n}$ or α>m+γ1$\alpha > m + \gamma -1$ or α=m+γ1$\alpha = m + \gamma -1$ and μ>μ$\mu >\mu ^*$ system (1.1) possesses a global bounded classical solution for any sufficiently smooth initial data.…”
Section: Introduction and Presentation Of The Main Resultsmentioning
confidence: 99%
“…The proof of Lemma 2.2 is similar to the proof of [15,Lemma 2.2]. Furthermore, to make the paper self-contained we provide some basic inequalities.…”
Section: Lemma 22 Under the Assumption Of Lemma 21 And For Any Nonneg...mentioning
confidence: 93%
“…We should mention that recently, some global existence results and large time behavior of solutions have also been established for the classical Keller-Segel model, both for the quasilinear parabolic-parabolic and parabolic-elliptic chemotaxis-growth system with nonlinear signal production, one can refer to the literatures [10,36,38,37]. However, to the best of our knowledge, until now there are no results for stabilization of quasilinear chemotaxis model of multiple sclerosis with nonlinear signal secretion, especially, for the case τ = 0.…”
mentioning
confidence: 99%
“…Boundedness for multiple sclerosis chemotaxis model with τ = 0. In this section, based on the ideas of [36] and [37], we proceed to derive the main step towards our boundedness proof with τ = 0. Let us first concentrate on the case that m < 1 + 2 N − l − r 2 .…”
mentioning
confidence: 99%